A dance with dragons - Martin, George R.R. (New York : Bantam Books, 2011)
In the aftermath of a colossal battle, Daenerys Targaryen rules with her three dragons as queen of a city built on dust and death. But Daenerys has thousands of enemies, and many have set out to find her. Fleeing from Westeros with a price on his head, Tyrion Lannister, too, is making his way east-- with new allies who may not be the ragtag band they seem. And in the frozen north, Jon Snow confronts creatures from beyond the Wall of ice and stone, and powerful foes from within the Night's Watch. In a time of rising restlessness, the tides of destiny and politics lead a grand cast of outlaws and priests, soldiers and skin changers, nobles and slaves, to the greatest dance of all.
Keywords: FANTASY -- FICTION